PENYESUAIAN DIRI ANAK-ANAK DI LINGKUNGAN SEKOLAH - Johari Marjan; Muhammad Zoher Hilmi (Universitas Hamzanwadi, 2020)
Self-adjustment is the basis for the formation of a child's personality. So that the ability to adjust for children is very necessary in the school environment. The purpose of this article is to know the importance of self-adjustment, knowing the determinants of successful adjustment and knowing the efforts to maximize children's adjustment in the school environment.